Enantiopure 3-Amino-Substituted 1-Indanones, 1-Tetralones, and 1-Benzosuberones via Friedel–Crafts Cyclisation of ω-Aryl-β-benzamido Acids - Davies, Stephen G.; Goddard, Euan C.; Roberts, Paul M.; Russell, Angela J.; Thomson, James E. (Synlett, 2015)
Conjugate addition of enantiopure lithium (R)-N-benzyl-N-(α-methylbenzyl)amide to a range of ω-aryl-α,β-unsaturated esters gives the corresponding ω-aryl-β-amino esters as single diastereoisomers in high yields. Friedel–Crafts cyclisation of the pendant carbonyl group onto the ω-aryl ring then gives a range of 3-amino-substituted 1-indanones, 1-tetralones, and 1-benzosuberones, representing an efficient and short protocol for the preparation of these benzo-fused carbocycles in enantiopure form.
Keywords: 1-benzosuberone; conjugate addition; Friedel–Crafts; 1-indanone; 1-tetralone